Factors Affecting Job Satisfaction of BumDesa Heads in the District of Bogor, West Java, Indonesia - Baban Sarbana; Herman (The Indonesian Forestry Certification Cooperation, 2023)
Mandated by Law No. 6 / 2014, the establishment of Village-Owned Enterprises (BUMDesa) aims to promote the welfare of rural communities by providing decent work and improving economic management and growth at the village level in line with Sustainability Development Goals (SDGs). Job satisfactions of BUMDesa’s heads play a crucial role in ensuring that those aims are realized. This study analyzes factors affecting BUMDesa’s heads in the district of Bogor, West Java, Indonesia. Data were collected by use of questionnaire interviews with 243 active heads of BUMDesa. The Structural Equation Model (SEM) was applied using the Lisrel 8.70 software. Four variables, i.e. salary/wages, supervision, co-workers and the job itself, were analyzed. The results show that salary/wages have the lowest indicator value, meaning that BUMDesa’s heads are statistically dissatisfied with the level of their salary/wages. On the contrary, BUMDesa’s heads are shown to be satisfied by their coworkers’ performance. Higher level governments need to assist village governments to adopt a fairer remuneration structure to improve job satisfaction, and hence, the performance of BUMDesa.